2017
DOI: 10.14260/jemds/2017/639
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anaesthesia Using Isobaric Levobupivacaine Alone and With Fentanyl for Lower Abdominal Surgery- A Randomised Double Blinded Controlled Trial

Abstract: BACKGROUND Levobupivacaine has equal potency as bupivacaine but lower CVS and CNS toxicity. Aim was to evaluate clinical efficacy of isobaric levobupivacaine with or without fentanyl in spinal anaesthesia for inguinal hernia surgeries regarding sensory-motor block characteristics, haemodynamic profile and complications. MATERIALS AND METHODS After approval from institutional ethical committee (IEC) and informed written consent, a randomised double blinded controlled trial was conducted during 1 year period. 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Verma et al (12) showed that adding fentanyl to intrathecal levobupivacaine in lower abdominal surgeries had effective sensory-motor blockade for a sufficient duration with stable hemodynamics. Narcotics have undesired effects such as vomiting and pruritis.…”
Section: Discussionmentioning
confidence: 99%
“…Verma et al (12) showed that adding fentanyl to intrathecal levobupivacaine in lower abdominal surgeries had effective sensory-motor blockade for a sufficient duration with stable hemodynamics. Narcotics have undesired effects such as vomiting and pruritis.…”
Section: Discussionmentioning
confidence: 99%
“…15-20 mg isobaric 0.5% levobupivacaine is considered to be the intrathecal dosage. 18 Bupivacaine is a local anesthesia that is commonly used as spinal anesthetic due to its great efficacy and lack of neurotoxicity. Because of its equivalent potency and lower neurotoxic and cardiotoxic effects, levobupivacaine is becoming more popular as an alternative for bupivacaine.…”
Section: Discussionmentioning
confidence: 99%